Comparative analysis of frictional behavior and mechanism of molybdenum ditelluride with different structures - Lina Zhang; Xinfeng Tan; Jianguo Jiao; Dan Guo; Jianbin Luo (Friction)
Abstract Two-dimensional (2D) transition metal dichalcogenides (TMDCs) have layered structures with excellent tribological properties. Since the energy difference between hexagonal-molybdenum ditelluride (2H-MoTe2) and distorted octahedral-molybdenum ditelluride (1T’-MoTe2) is very small among the transition metal dichalcogenides (TMDCs), MoTe2 becomes one of the most promising candidates for phase engineering. In our experiment, we found that the friction force and friction coefficient (COF) of 2H-MoTe2 were an order of magnitude smaller than those of 1T’-MoTe2 by the atomic force microscope (AFM) experiments. The friction difference between 1T’-MoTe2 and 2H-MoTe2 was further verified in molecular dynamics (MD) simulations. The density functional theory (DFT) calculations suggest that the friction contrast is related to the difference in sliding energy barrier of the potential energy surface (PES) for a tip sliding across the surface. The PES obtained from the DFT calculation indicates that the maximum energy barrier and the minimum energy path (MEP) energy barrier of 2H-MoTe2 are both smaller than those of 1T’-MoTe2, which means that less energy needs to be dissipated during the sliding process. The difference in energy barrier of the PES could be ascribed to its larger interlayer spacing and weaker Mo–Te interatomic interactions within the layers of 2H-MoTe2 than those of 1T’-MoTe2. The obvious friction difference between 1T’-MoTe2 and 2H-MoTe2 not only provides a new non-destructive means to detect the phase transition by the AFM, but also provides a possibility to tune friction by controlling the phase transition, which has the potential to be applied in extreme environments such as space lubrication.